Evaluation of sunnhemp (Crotalaria juncea) genotypes for high fibre yield - CHAUDHARY, BABITA; TRIPATHI, M K; BHANDARI, HEM RAJ; PANDEY, S K; MEENA, D R; PRAJAPATI, S P (The Indian Journal of Agricultural Sciences, 2015)
Four genetically different genotypes of sunnhemp (Crotalaria juncea L.) were evaluated for fibre yield and its yield component traits for three years 2008-2009 to 2010-2011 at Sunnhemp Research Station, Pratapgarh, Uttar Pradesh. Significant differences among experimental genotypes were recorded for fibre yield and its attributes. High fibre yield/ha was recorded for SUIN-029 (9.06 q/ha) followed by SUIN-80 (8.94 q/ha). The highest green biomass yield (337.30 q/ha) and stick yield (52.41 q/ha) were recorded for SUIN-029. The analysis of the data for all years revealed superiority of genotype SUIN-029 for most of the fibre yield traits. This genotype can be used as donor for future breeding programme.